Neraca kehidupan kutukebul Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) pada tanaman cabai dan gulma babadotan pada suhu 25 °C dan 29 °C - Subagyo, Vani Nur Oktaviany; Hidayat, Purnama (Jurnal Entomologi Indonesia, 2014)
Bemisia tabaci (Gennadius) is an important pest on horticultural crops that can also become a vector of Geminivirus that transmit the yellow curl disease. B. tabaci can also attack weeds that grow around the field such as Ageratum conyzoides or goatweed. The objective of this research was to study the life cycle, life time, fecundity, and reproduction rate of B. tabaci on chili pepper and goatweed. The experiment was conducted by observing the development of 50 eggs into adulthood. All 50 eggs were put on one plant and repeated 3 times. The plants were grown at temperatures 25 °C and 29 °C inside growth chamber (L : D = 12 : 12). The result of this experiments showed that at both temperatures of 25 °C and 29 °C, reproductive rate (R0), intrinsic rate of increase (r) and fecundity of B. tabaci were higher on goatweed than chili pepper. This implies that the existence of goatweed around chili pepper in the field can serve as a good alternative host for B. tabaci, hereby supporting the pest population even further.